32. Linac based VMAT radiosurgery for multiple brain lesions: comparison between a conventional multi-isocenter approach and a new dedicated mono-isocenter 4π technique (HyperArc™). (December 2018) - Ruggieri, R.; Naccarato, S.; Ricchetti, F.; Mazzola, R.; Fiorentino, A.; Alongi, F.
Abstract : Purpose: Linac based VMAT radiosurgery (SRS) of multiple brain lesions (MBL) is typically performed by a multiple-isocenter approach, i.e.one isocenter per lesion.Here we present the worldwide first experience with a new mono-isocenter technique with multiple non-coplanar arcs (HyperArc, Varian Inc.)in terms of a plan comparison with a multiple-isocenter approach. Methods: From August to October 2017, 20 patients with MBL (mean 5, range 2–10) have been treated by HyperArc: prescribed doses ( D p ) were 18–25 Gy in single-fraction, and 21–27 Gy in three-fractions.Total PTV, defined by a 2 mm isotropic margin from each lesion, had mean size of 9.6 cm 3 (range 0.5–27.9 cm 3 ).HyperArc VMAT plans (HA), with 5 non-coplanar 180°-arcs (couch at 0°, ±45°, ±90°), and multiple-isocenter VMAT plans (RA), with 2 coplanar 360°-arcs per isocenter, were generated.100% D p at 98%PTV was prescribed, and D 2 % (PTV)<150% D p was accepted.Constraints for 1(3) -fraction to the brainstem, D 0.5cc <10(18) Gy, and to the optical nerves/chiasm, eyes and lenses, D 0.5cc < 8(15) Gy, had to be fulfilled.The metrics used for plan comparison were Paddick conformity (CI) and gradient (GI) index, V 12 and mean dose to the brain-minus-PTV, MU and overall treatment time (OTT) per fraction.OTT was measured for HA treatments, whereas estimated (3 min.for patient setup plus 5 min.for each CBCT per isocenter) for RA plans. Results: As detailed inTable 1, HA plans resulted in significantly improved CI ( p <.0001), GI ( p = .0003), V 12 to the brain-minus-PTV ( p = .023), MU ( p <.0001) and OTT ( p <.0001).In Fig.1, the typical restriction of the 50% D p isodose shells around the targets for the HA plans is depicted for an example patient.By contrast, no significant difference in terms of mean doses to the brain-minus-PTV resulted ( p = .31). Conclusions: For linac based VMAT-SRS of MBL, HyperArc plans assured a higher CI and a lower GI, a lower V 12 to the brain-minus-PTV, and a lower OTT than standard multiple-isocenter VMAT plans. Finally, all HyperArc treatments were completed within a typical 20 min. time slot.